Studies in Mexican grasshoppers: four new species of the genus Oaxaca Fontana, Buzzetti & Mariño-Pérez, 2011 with the erection of the subgenus Paraoaxaca (Caelifera: Acrididae: Melanoplinae) - Aguilar-Roldán, César Antonio; Gómez-Tapia, José David; Mariño-Pérez, Ricardo; Song, Hojun; Vázquez-Reyes, Leopoldo D.; Sanabria-Urbán, Salomón (Zootaxa, 2024)
After a thoughtful review of 159 specimens collected from 17 localities from multiple collections in Mexico and the U.S.A. spanning decades of collecting events, four new species of the micropterous Melanoplinae genus Oaxaca are described from Southwestern Mexico. Based on morphological analyses, we placed these four species within the group Paraoaxaca subgen. nov. The four species are Oaxaca (Paraoaxaca) ottei sp. nov., Oaxaca (Paraoaxaca) cohni sp. nov., Oaxaca (Paraoaxaca) cuitlateca sp. nov., and Oaxaca (Paraoaxaca) tlapaneca sp. nov. We further discussed the body of evidence that led us to the erection of this new subgenus within the genus Oaxaca and the future directions needed to disentangle the internal relationships with the genus Oaxaca and their sister groups. This contribution is a continuation of a series of works dealing with the specious orthopterofauna of the region that has been started thanks to the efforts of recent collection events and careful review of unsorted material deposited in legacy collections.